Tyrosine kinase inhibitors in patients with chronic myelogeneous leukemia: defining the role of social risk factors and non-adherence to treatment - Okumura LM; Antunes VD; Aguiar KS; Farias T; Andrzejevski VM; Funke VM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objective: To assess the role of social risk factors on adherence to tyrosine kinase inhibitors (TKI) therapy in chronic myeloid leukemia (CML) patients. Methods: This is a retrospective study and eligible patients were adults with CML on TKI treatment. Cases of no adherence to treatment were confirmed during pharmacists' consultation (patient-reported adherence). Baseline characteristics between groups were compared between cases and controls groups. Risk factors identified in bivariate analysis (p<0.2) were included in multivariate model. A qualitative investigation assessed whether such predictors of non-adherence had causal relationship. Results: Of 151 patients with CML consulted by pharmacists, 21% had adherence problems. Despite patients with secondary school (p=0.03), most of investigated social risk factors did not differ between groups. However, by using a qualitative approach, patients' level of education could not explain low adherence rates behavior. Conclusions: Social determinants of health, herein investigated, were unlikely to predict adherence to treatment. Regression techniques may lead to untrue statements, so future researches should consider investigating the causes, not only the statistical estimates.